2022
DOI: 10.2217/imt-2021-0149
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Eosinophil Count is Associated with Response to Chemoimmunotherapy in Metastatic Triple-Negative Breast Cancer

Abstract: Introduction: There is evidence for an association between peripheral blood eosinophil count (PBEC) and response to cancer immunotherapy; however, such data is limited in metastatic triple-negative breast cancer (mTNBC). Patients & methods: This report presents patients (n = 14) who received a combination of durvalumab and paclitaxel for mTNBC (NCT02628132). Results: There was a statistically significant correlation (p = 0.028) between an increase in PBEC (>300/mm3) during treatment and response to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Reportedly, elevated peripheral blood eosinophil counts (PBECs) are associated with a better response during immunotherapy for metastatic triple-negative breast cancer. 20 Therefore, we intended to explore the association between changes in PBECs during treatment and the clinical response. Survival analysis revealed a statistically significant association between elevated PBECs during treatment and longer survival outcome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, elevated peripheral blood eosinophil counts (PBECs) are associated with a better response during immunotherapy for metastatic triple-negative breast cancer. 20 Therefore, we intended to explore the association between changes in PBECs during treatment and the clinical response. Survival analysis revealed a statistically significant association between elevated PBECs during treatment and longer survival outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a positive association between eosinophil invasion of tumor tissue or an increase in PBEC and superior response to ICIs in several types of cancer has been reported. 20 , 37 Although the underlying mechanism is not fully understood, there is strong evidence that eosinophils exhibit antitumor effects. Thus, eosinophils affect the immune response to diseases such as cancer, and predictive biomarkers that reflect this inflammatory response to treatment may be useful for clinical decision-making in the management of patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observational studies suggested that early changes of the peripheral blood markers could aid in prognosis prediction in-ICI treated patients with reflecting host–tumor interactions and host immune activation [ 62 , 63 ]. The response rates were better in patients with lymphocyte or eosinophil expansion under ICIs [ 31 , 64 , 65 , 66 ]. In contrast, a lower benefit with ICIs would be expected in patients with neutrophilic expansion due to protumorigenic and immunosuppressive properties of neutrophils secondary to the secretion of increased progranulopoietic cytokines and blunting of T-cell antitumor responses [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer, in particular, may be associated with an increased risk of eosinophilia when treated with ICIs compared to other cancers 12 . In addition, the combination of ICIs, or combination with paclitaxel chemotherapy may increase eosinophilia compared to the monotherapy of ICI 13,14 . Although a high eosinophil count alone may not necessarily serve as an index of severity, 11 clinicians should account for the possibility of the development of severe eosinophilia in patients treated with nivolumab and ipilimumab, which are increasingly utilized in patients with lung cancer, as severe eosinophilia could be the sign of severe irAE.…”
Section: Discussionmentioning
confidence: 99%